2019
DOI: 10.1097/nne.0000000000000739
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students' Perceptions of Just Culture in Nursing Programs

Abstract: Background While just culture is embraced in the clinical setting, just culture has not been systematically incorporated into nursing education. Purpose The purpose of this study was to assess prelicensure nursing student perceptions of just culture in academia. Methods Following a quantitative, descriptive design, the Just Culture Assessment Tool for Nursing Education (JCAT-NE) was used to measure just cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 13 publications
0
39
3
Order By: Relevance
“…During development, painstaking actions were taken to remain true to the original JCAT instrument’s 27 items while making the modifications needed so that the newly developed JCAT-NE used language that aligned with the academic experience of nursing students. The JCAT-NE was then validated as a tool to measure just culture in academia and a small pilot study using the instrument with 133 students demonstrated the reliability of the JCAT-NE with a Cronbach’s α = 0.75 (Walker et al., 2020). A larger, multi-site study administered the JCAT-NE to 849 students at 15 nursing schools across the United States and found significant differences in the perceptions of students based on whether they were at the beginning, middle or end of their nursing education programme (Walker et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…During development, painstaking actions were taken to remain true to the original JCAT instrument’s 27 items while making the modifications needed so that the newly developed JCAT-NE used language that aligned with the academic experience of nursing students. The JCAT-NE was then validated as a tool to measure just culture in academia and a small pilot study using the instrument with 133 students demonstrated the reliability of the JCAT-NE with a Cronbach’s α = 0.75 (Walker et al., 2020). A larger, multi-site study administered the JCAT-NE to 849 students at 15 nursing schools across the United States and found significant differences in the perceptions of students based on whether they were at the beginning, middle or end of their nursing education programme (Walker et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The JCAT-NE was then validated as a tool to measure just culture in academia and a small pilot study using the instrument with 133 students demonstrated the reliability of the JCAT-NE with a Cronbach’s α = 0.75 (Walker et al., 2020). A larger, multi-site study administered the JCAT-NE to 849 students at 15 nursing schools across the United States and found significant differences in the perceptions of students based on whether they were at the beginning, middle or end of their nursing education programme (Walker et al., 2020). The factor analysis supports further refinement of the JCAT-NE as a valid and reliable instrument to assess students’ perceptions of just culture within their nursing education programmes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations